When "Good Evidence" Is Not Enough: A Case of Global Malaria Policy Development. Issue 9 (22nd March 2018) - D'Souza, Bianca J.; Parkhurst, Justin O.
Abstract: This paper presents findings from a case study of two different policy development processes within the WHO's malaria department. By comparing the policy processes for the interventions of intermittent preventive treatment in infants versus children, the findings suggest that "good evidence" from a technical perspective, though important, is not sufficient to ensure universal agreement and uptake of recommendations. An analysis of 29 key informant interviews finds that evidence also needs to be relevant to the policy question being asked, and that expert actors retain a concern over the legitimacy of the process by which technical evidence is brought to bear in the policy development process. Previous findings from the field of sustainable development, that evidence must be credible, salient, and legitimate to be accepted by the public, appears to apply equally within scientific advisory committees. While the WHO has principally focused on technical criteria for evidence inclusion in its policy development processes, this study suggests that the design and functionality of its advisory bodies must also enable transparent, responsive, and accepted processes of evidence review to ensure that these bodies are effective in producing advice that engenders change in policy and practice. Abstract : While the WHO has principally focused on technical criteria for evidence inclusion in its policy development processes, findings suggest that the design and functionality of its advisory bodies must also enable transparent, responsive, and accepted processes of evidence review. Previous findings that evidence must be credible, salient, and legitimate to be accepted by the public, appear to apply equally within scientific advisory committees.